3D-Modellierung der Dogger-Malm Grenze im Raum Bad Staffelstein, abgeleitet aus Lineamentanalyse und Strukturkarte - Wehrl, Michael; Rohn, Joachim; de Wall, Helga (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2016)
In dieser Arbeit wird im Rahmen des Projekts »Erkundung des geologischen Untergrunds in Nordost-Bayern als Grundlage zur Bewertung des geothermischen Potentials« die Höhenlage der Dogger/Malm-Grenze untersucht. Dazu werden aus bestehenden amtlichen, geologischen Karten (GK), sowie digitalen Geländemodellen (DGMs) Strukturkarten dieser geologischen Grenze erstellt und als 3D-Modell dargestellt. Dafür werden geologische Karten und DGM-Daten ausgewertet, deutlich an der Oberfläche ausstreichende Störungen erfasst und der Verlauf der Grenze anhand der Geländemorphologie in Form von einzelnen Höhenpunkten (HP) eingezeichnet. Dabei ist zu beachten, dass die wahre Grenze oftmals durch Ablagerungen von Massenbewegungen überlagert wird, weshalb diese Ablagerungen zusätzlich erfasst werden müssen. Da die Abrisse meist großen Klüften folgen, können diese auch in die Karte aufgenommen werden. Daraufhin werden Homogenbereiche festgelegt, in denen das Gebiet von Störungen unbeeinflusst ist. Auf diese Weise wurde eine tektonische Übersichtskarte des Untersuchungsgebietes erstellt. Dort können schließlich Höhenpunkte gleicher Höhenlage verbunden und so Strukturlinien eingezeichnet werden. Durch Parallelverschiebung werden aus einer Linie und weiteren Punkten zusätzliche Linien generiert. Unterbrochene oder scharf umbiegende Linien sind Indizien für bislang unbekannte Verwerfungen im Untergrund. Aus den so gewonnenen Daten wird ein 3D-Modell erstellt, das die tektonische Situation im Untersuchungsgebiet wiederspiegelt.
Keywords: 3D-Modellierung; Streichkurven; Dogger/Malm-Grenze

Calculating energy and its spatial distribution for a subsurface urban heat island using a GIS-approach - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Geosciences, 2021)
In urban areas, the human influence on the city-ecosystem often results in a Subsurface Urban Heat Island (SUHI), which can be used geothermally. Unfortunately, a model of a SUHI does not consider the geology and hydrogeology of the subsoil. These can vary significantly over short distances, and are of considerable importance for the energy balance. In this work, we calculated the energy and its density stored in the subsoil via a SUHI. For this so-called energy-SUHI (e-SUHI), we evaluated the geology and its physical parameters for the first 20 m below ground level in the German city of Nuremberg and linked them to measured underground temperatures in a GIS application. This approach revealed stored energy of 1.634 × 1010 MJ within the soil and water for the study area with an area of 163 km2 and a volume of 3.26 × 109 m3. It corresponds to an average energy density of 5.0 MJ/m3. The highest energy density of 16.5 MJ/m3 was found in the city center area and correlated well to increases in subsurface temperature. As expected, our model reacts sensitively to thickness changes in the geological layers and the unsaturated zone.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Energy-SUHI; Geothermal energy; GIS; Subsurface Urban Heat Island (SUHI)

Detecting Groundwater Temperature Shifts of a Subsurface Urban Heat Island in SE Germany - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Water, 2021)
The subsurface beneath cities commonly shows a temperature anomaly, a so-called Subsurface Urban Heat Island (SUHI), due to anthropogenic heat input. This excess heat has multiple effects on groundwater and energy resources, such as groundwater chemistry or the efficiency of geothermal systems, which makes it necessary to investigate the temporal development of a SUHI. For this purpose, temperature profiles of 38 observation wells in the German city of Nuremberg were evaluated from 2015 to 2020 and the measured temperature changes were linked to the surface sealing. The results show that the groundwater temperatures changed between -0.02 K/a and +0.21 K/a, on average by +0.07 K/a during this period. A dependence between the temperature increase and the degree of sealing of the land surface was also observed. In areas with low surface sealing of up to 30% the warming amounts were 0.03 K/a on average, whereas in areas with high sealing of over 60% significantly higher temperature increases of 0.08 K/a on average were found. The results clearly emphasize that the subsurface urban heat island in its current state does not represent a completed process, but that more heat energy continues to enter the subsoil within the city than is the case with near-natural land surfaces.
CRIS-Team WoS Importer:2021-06-04